Observation of interest in the surgical treatment of hiatal hernia - Arpayoglou, Alejandro; Crestanello, Francisco; Rubio, Roberto (Cirugía del Uruguay, 1975)
A patient with a sliding esophageal hiatal hernia with chronic digestive bleeding was operated upon by an abdominal approach, with Nissen's technique of fundoplication. His symptomatology of gastroesophageal reflux disappeared, but the bleeding persisted. A roentgenologic control showed that the plicated upper end of the stomach remained in the thorax. The authors discuss the origin of the persisting hemorrhage, concluding that the ectopic stomach was bleeding by a still obscure pathogenic mechanism. The patient was re-operated upon by a left thoracic approach; the fundoplication was undone and the stomach was replaced in the abdomen, fixing it according to Allison's technique. The bleeding was arrested and the patient was in good conditions two months and a half after. surgery.